Long-term effectiveness and safety of femoropopliteal drug-coated balloon angioplasty: 5-year results of the randomized controlled EffPac trial - Teichgräber, Ulf; Lehmann, Thomas; Ingwersen, Maja; Aschenbach, René; Zeller, Thomas; Brechtel, Klaus Franz Martin; Blessing, Erwin; Lichtenberg, Michael Klaus William; von Flotow, Peter; Heilmeier, Britta; Sixt, Sebastian; Brucks, Steffen; et al. (CardioVascular and interventional radiology, 2022)
This study aimed to assess 5-year effectiveness and safety of femoropopliteal angioplasty with the Luminor® 35 drug-coated balloon (DCB).